The Strategic Approach to Solve the Poverty in Developing Country - Dahroni, D (Forum Geografi, 1991)
Not only does poverty in developing country face decline of relative imbalance, but they face the increasing of absolute poverly as well. One of the characteristic of developing country is signed by growth population rapidly. Economic development prospect doesnât apart from ratio between quantity of population and land suitability. The limitedness of land that be done by farmer cause the decline of agriculture production, besides, the growth of wotk opportunity increase, the employment is restricted. Some mainÂ  problems that must be faced by now are; the distribution of income, work opportunity, man power quality, and many alternative approach to be sub mitted to reach the economic growth by distribution.